2022
DOI: 10.1038/s41467-022-30516-z
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an intermediate state during lithium intercalation of twisted bilayer MoS2

Abstract: Lithium intercalation of MoS2 is generally believed to introduce a phase transition from H phase (semiconducting) to T phase (metallic). However, during the intercalation process, a spatially sharp boundary is usually formed between the fully intercalated T phase MoS2 and non-intercalated H phase MoS2. The intermediate state, i.e., lightly intercalated H phase MoS2 without a phase transition, is difficult to investigate by optical-microscope-based spectroscopy due to the narrow size. Here, we report the stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In addition, three characteristic peaks were visible at J 1 , J 2 , and J 3 , and the 1T phase exhibited a zone-folding process. These three peaks were assumed to be caused by MoS 2 , indicating that the prepared MoS 2 was a mixed phase. ,, The Raman spectra of SWCNTs had a weak D-band at 1343 cm –1 and a strong G-band at 1596 cm –1 . The G-band is characteristic of the in-plane stretching vibration of sp 2 hybrid carbon atoms, whereas the D-band is connected to the resonant scattering generated by structural flaws.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, three characteristic peaks were visible at J 1 , J 2 , and J 3 , and the 1T phase exhibited a zone-folding process. These three peaks were assumed to be caused by MoS 2 , indicating that the prepared MoS 2 was a mixed phase. ,, The Raman spectra of SWCNTs had a weak D-band at 1343 cm –1 and a strong G-band at 1596 cm –1 . The G-band is characteristic of the in-plane stretching vibration of sp 2 hybrid carbon atoms, whereas the D-band is connected to the resonant scattering generated by structural flaws.…”
Section: Resultsmentioning
confidence: 99%
“…Earth-abundant molybdenum disulfide (MoS 2 ), an inorganic compound with a stable semiconducting 1H phase and a sub-stable metallic 2T phase, has been considered as a promising candidate for TE applications due to its high S (≈10 mV K –1 ). However, MoS 2 has a low electrical conductivity (≈2.2 × 10 –6 S cm –1 ) . Guo et al reported that pressure-induced semiconductor/metal transition was beneficial for improving the electrical conductivity .…”
Section: Introductionmentioning
confidence: 99%
“…3f that the monolayer catalyst shows a very similar ECSA value and that the 1T/2H interfacial junctions could have a positive effect on promoting both the NRR and HER kinetics. 17,20,26…”
Section: Resultsmentioning
confidence: 99%
“…The abundant saturated coordinative atoms in the base planes, on the other hand, are inactive and the overall catalytic efficiency is severely slowed by a deficiency of active sites on the basical plane. 20 To this end, defect, phase and strain engineering have been explored to boost the intrinsic activity of MoS 2 catalysts. 21–24 However, their poor conductivity and inert basal planes result in NH 3 yield rates that are generally less than 50 μg h −1 mg cat −1 , such as 13.09 μg h −1 mg cat −1 for MoS 2 nanosheets and 29.28 μg h −1 mg cat −1 for defect-rich 2H-MoS 2 nanoflowers.…”
Section: Introductionmentioning
confidence: 99%
“…In the 2H phase of MoS 2 , the Mo atom is surrounded in trigonal prismatic coordination with two S-Mo-S units per elemental cell [20]. Considerable effort has been made to study the H-phase MoS 2 in the fields of electronics, photonics, and photo-catalytic chemistry [21]. Molybdenum selenide (MoSe 2 ) has also been extensively researched due to its strong absorption of sunlight and unique band structure while molybdenum telluride (MoTe 2 ) is gaining interest in electronic and optoelectronic devices [22].…”
Section: Introductionmentioning
confidence: 99%